What if it happens in my classroom? : developing skills for expert behavior management - Sida-Nicholls, Kate. (New York : c)
Why can't I stop my students from being noisy as they leave my classroom? What can I do when a student is texting on their phone in my lesson? How can I stop a student from constantly tapping their pen while I am talking?Sound familiar?Chewing gum, dropping litter, swearing, late homework and disruptive behaviour in class are just a few of the issues that teachers have to face every day in the classroom. How you choose to respond to these incidents, however minor they may first seem, can have a dramatic impact on the overall quality of your lessons. There is no one answer to behaviour and clas.
Includes index.
Keywords: Classroom management; Behavior modification; Problem children -- Behavior modification; School discipline